2012
DOI: 10.1111/j.1539-6924.2011.01785.x
|View full text |Cite
|
Sign up to set email alerts
|

The Health Impact of Mandatory Bicycle Helmet Laws

Abstract: This article seeks to answer the question whether mandatory bicycle helmet laws deliver a net societal health benefit. The question is addressed using a simple model. The model recognizes a single health benefit--reduced head injuries--and a single health cost-increased morbidity due to foregone exercise from reduced cycling. Using estimates suggested in the literature on the effectiveness of helmets, the health benefits of cycling, head injury rates, and reductions in cycling leads to the following conclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…Numerous of these kinds of risk analyses exist in other research traditions, which are mostly applied to determine safety risks and risks in project management (e.g., Keeney and Von Winterfeldt 2011;De Jong 2012). In risk analysis, a risk can be defined as the probability for some adverse effect to occur given some conditions (risk factors).…”
Section: Risk Analysismentioning
confidence: 99%
“…Numerous of these kinds of risk analyses exist in other research traditions, which are mostly applied to determine safety risks and risks in project management (e.g., Keeney and Von Winterfeldt 2011;De Jong 2012). In risk analysis, a risk can be defined as the probability for some adverse effect to occur given some conditions (risk factors).…”
Section: Risk Analysismentioning
confidence: 99%
“…Some countries have or debate mandatory helmet wearing laws, which are criticized for putting an (additional) burden on cyclists (Robinson, 2003). Overall, evidence on helmet laws is insufficient to weigh desired injury prevention effects against unintended effects of less people cycling (De Jong, 2012;Fyhri, Bjørnskau, & Backer-Grøndahl, 2012;Grant & Rutner, 2004;Robinson, 2006).…”
Section: Crash Risk From Cyclingmentioning
confidence: 99%
“…This research was motivated by the recent announcement of this possibility by the Spanish Government. It has been reported that compulsory helmets can result in a decrease in the number of cyclist [28,29], specifically in public bike schemas [30]. In order to confirm and estimate this potential decline in the number of bicyclists in Sevilla, we conducted a survey over 527 cyclists (344 on private bikes and 183 on public bikes) on 13 representative points of the cycle network along November and December of 2013.…”
Section: Future Trendsmentioning
confidence: 99%